Recombinant erythropoietin does not augment hypothermic white matter protection after global cerebral ischaemia in near-term fetal sheep. Issue 3 (29th July 2021) - Wassink, Guido; Davidson, Joanne O; Crisostomo, Alyssa; Zhou, Kelly Q; Galinsky, Robert; Dhillon, Simerdeep K; Lear, Christopher A; Bennet, Laura; Gunn, Alistair J
Abstract: Therapeutic hypothermia for hypoxic-ischaemic encephalopathy provides partial white matter protection. Recombinant erythropoietin reduces demyelination after hypoxia-ischaemia, but it is unclear whether adjunct erythropoietin treatment can further improve outcomes after therapeutic hypothermia. Term-equivalent fetal sheep received sham-ischaemia ( n  = 9) or cerebral ischaemia for 30 min (ischaemia-vehicle, n  = 8), followed by intravenous infusion of recombinant erythropoietin (ischaemia-Epo, n  = 8; 5000 IU/kg bolus dose, then 833.3 IU/kg/h), cerebral hypothermia (ischaemia-hypothermia, n  = 8), or recombinant erythropoietin plus hypothermia (ischaemia-Epo-hypothermia, n  = 8), from 3 to 72 h post-ischaemia. Foetal brains were harvested at 7 days after cerebral ischaemia. Ischaemia was associated with marked loss of total Olig2-positive oligodendrocytes with reduced density of myelin and linearity of the white matter tracts ( P  < 0.01), and microglial induction and increased caspase-3-positive apoptosis. Cerebral hypothermia improved the total number of oligodendrocytes and restored myelin basic protein ( P  < 0.01), whereas recombinant erythropoietin partially improved myelin basic protein density and tract linearity. Both interventions suppressed microgliosis and caspase-3 ( P  < 0.05). Co-treatment improved 2′, 3′-cyclic-nucleotide 3′-phosphodiesterase-myelin density compared to hypothermia, but had no other additive effect. These findings suggest that although hypothermia and recombinant erythropoietin independently protect white matter after severe hypoxia-ischaemia, they have partially overlapping anti-inflammatory and anti-apoptotic effects, with little additive benefit of combination therapy. Abstract : Wassink et al. report that in near-term fetal sheep induced hypothermia and high-dose recombinant erythropoietin infusion started 3 h after cerebral ischaemia and continued for 3 days, independently protected white matter after 7 days recovery. However, there were overlapping anti-inflammatory and anti-apoptotic effects, with little additive benefit of combination therapy. Graphical Abstract: